Austria : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report, 2010)
Austria's recession had limited effects on unemployment. Investment declined sharply but consumption helped cushion the recession, supported by tax cuts and various labor market measures together with large increases in real wages. Austria's fiscal position has weakened significantly in recent years, although to a lesser extent than the euro area average. The authorities' plan to embark on a decisive fiscal consolidation path is welcomed. They recognized, however, that reducing the share of foreign exchange loans, while providing continued financing to central and southeastern Europe, will be challenging.